Data-driven combinatorial optimization for sensor-based assessment of near falls - Kammerdiner, Alla R.; Guererro, Andre N. (Annals of operations research, 2019)
Falls represent a considerable public health problem, especially in older population. We describe and evaluate data-driven operations research models for detection and situational assessment of falls and near falls with a system of wearable sensors. The models are formulated as instances of the multidimensional assignment problem. Our computational studies provide some initial empirical evidence of the potential usefulness of this new application of the multidimensional assignment problem.